Interplay between Caveolin-1 and body and tumor size affects clinical outcomes in breast cancer - Christopher Godina; Vineesh Indira Chandran; Magdalena Barbachowska; Helga Tryggvadottir; Björn Nodin; Edward Visse; Signe Borgquist; Karin Jirström; Karolin Isaksson; Ana Bosch; Mattias Belting; Helena Jernström (Translational Oncology, 2022)
Background: Caveolin-1 (CAV1) is associated with cholesterol-rich membrane raft domains and is a master regulator of cell signaling and membrane transport. Here, we investigated CAV1’s role in cellular compartments of breast cancer in relation to signaling pathways, clinicopathological features, and clinical outcomes. Methods: CAV1 levels were evaluated with immunohistochemistry in cytoplasm of invasive tumor cells and stromal cells in tumor tissue microarrays from a cohort of 1018 breast cancer patients (inclusion 2002–2012, Sweden). Cytoplasmic and stromal CAV1 were categorized as positive/negative and strong/not strong, respectively. CAV1 expression in relation to clinical outcomes was assessed with Cox regression. Investigations into CAV1 functional pathways was conducted in the STRING, GOBO, and TCGA databases. Results: CAV1 expression was associated with non-luminal subtypes, cell cycle control, inflammation, epithelial-mesenchymal transition, and the IGF/Insulin system. Generally, CAV1 was not associated with recurrence risk. Stromal CAV1’s impact on recurrence risk was modified by BMI ≥25 kg/m2 (Pinteraction = 0.002), waist ≥80 cm (Pinteraction = 0.005), and invasive tumor size (pT2/3/4) (Pinteraction = 0.028). In low-risk patients only, strong stromal CAV1 significantly increased recurrence risk (HRsadj ≥1.61). In all patients, positive cytoplasmic CAV1 conferred >2-fold risk for contralateral disease HRadj 2.63 (95% CI 1.36–5.10). Strong stromal CAV1 conferred nearly 2-fold risk for locoregional recurrence HRadj 1.88 (95% CI 1.09–3.24). Conclusions: CAV1’s prognostic impact depended on its localization, anthropometric, and tumor factors. Stromal CAV1 predicted high recurrence risk in a group of supposedly ‘low-risk’ patients. Cytoplasmic CAV1 predicted metachronous contralateral disease. If confirmed, CAV1 could be used as treatment target and for risk-stratification.